2022
DOI: 10.3390/jmse10111607
|View full text |Cite
|
Sign up to set email alerts
|

On Cubic Spudcan Deep Penetration in Dense Sand Overlying Non-Uniform Clay

Abstract: Installing spudcans for jack-up rigs in a layered seabed with an interbedded strong-over-soft layer is challenging in the offshore industry due to possible punch-through failure. The methods currently used to predict punch-through failure mainly focus on generic spudcans, usually ignoring the geometric features of the spudcan. The aim of this study is to determine whether the punch-through potential of a generic spudcan is applicable to a cubic spudcan of a BH12# jack-up rig installed in dense sand overlying n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…To determine if the punch-through potential of a generic spudcan is applicable to a cubic spudcan of a BH12# jack-up rig in a layered seabed with an interbedded strong-oversoft layer, Zhao et al [8] developed a series of large deformation finite element models on dense sand overlying non-uniform clay using a generic spudcan and a cubic spudcan. It was found that the post-peak resistances of the cubic spudcan were higher than those of the corresponding generic spducan.…”
mentioning
confidence: 99%
“…To determine if the punch-through potential of a generic spudcan is applicable to a cubic spudcan of a BH12# jack-up rig in a layered seabed with an interbedded strong-oversoft layer, Zhao et al [8] developed a series of large deformation finite element models on dense sand overlying non-uniform clay using a generic spudcan and a cubic spudcan. It was found that the post-peak resistances of the cubic spudcan were higher than those of the corresponding generic spducan.…”
mentioning
confidence: 99%